Searching transnational relations between Moluccans in the Netherlands and the Moluccas - Steijlen, Fridus (UI Scholars Hub, 2022)
This article deals with the transnational relations between Moluccans in the Netherlands and the Moluccas. Former Moluccan colonial soldiers and their families were forced to go to the Netherlands because of political developments in Indonesia after the transfer of sovereignty in 1949. They hoped to return soon to an independent South Moluccan Republic but, more than seventy years later, they still live in the Netherlands. This article first describes how and why Moluccans came to the Netherlands and began to build a community. At the very beginning, the foundations for a transnational relationship were laid through village-based organizations and political organizations. After decades living in exile, the political dimension of the transnational relation assumed great prominence for most Moluccans, later to make place for a more varied transnational relation. The political ideal changed and its priority on the Moluccan “public agenda” dropped until in 1999 a new conflict flared up in the Moluccas. A renewed, altered political transnational relation emerged. The transnational relationship also simultaneously developed in more diverse ways, via development projects, cultural exchange, and the like. By this time, the position of Moluccans in the Moluccas in this transnational relation had also changed.